Solving Fuzzy Attribute Quality Control Charts with proposed Ranking Function - Thamer, Esraa Dhafer; Hussein, Iden Hasan (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
The attribute quality control charts are one of the main useful tools to use in control of quality product in companies. In this paper utilizing the statistical procedures to find the attribute quality control charts for through fuzzified the real data which we got it from Baghdad Soft Drink Company in Iraq, by using triangular membership function to obtain the fuzzy numbers then employing the proposed ranking function to transform to traditional sample. Then, compare between crisp and fuzzy attribute quality control.